2019
DOI: 10.2147/ijn.s224488
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ciprofloxacin Functionalized Biogenic Gold Nanoflowers as Nanoantibiotics Against Pathogenic Bacterial Strains</p>

Abstract: PurposeAntibiotics are currently being rendered non-functional by the rising incidence of multi-drug resistance amongst pathogenic bacteria. Research has now been focused on developing solutions to this problem by creating new antibiotics and enhancing the functionality of the existing ones.Patients and methodsIn the present study, ciprofloxacin was conjugated to biogenic gold nanoflowers (GNFs) from Bacillus subtilis RSB64 by a robust adsorption method under optimized conditions. The resultant drug–nanoflower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The release data obtained were fitted into the following equations. Q t : The released amount of propolis/dexpanthenol at time t, Q 0 : the initial amount of propolis/dexpanthenol, Q ∞ : the released amount of propolis/dexpanthenol at infinite time, k: the release constant of each model, n : the exponent, c: an intercept [ 71 , 72 ]. Zero-Order model: Q t /Q ∞ = kt + c First-Order model: Q t = Q 0 + kt Higuchi model: Q t /Q ∞ = kt ½ + c Korsmeyer-Peppas model: Q t /Q ∞ = kt n …”
Section: Methodsmentioning
confidence: 99%
“…The release data obtained were fitted into the following equations. Q t : The released amount of propolis/dexpanthenol at time t, Q 0 : the initial amount of propolis/dexpanthenol, Q ∞ : the released amount of propolis/dexpanthenol at infinite time, k: the release constant of each model, n : the exponent, c: an intercept [ 71 , 72 ]. Zero-Order model: Q t /Q ∞ = kt + c First-Order model: Q t = Q 0 + kt Higuchi model: Q t /Q ∞ = kt ½ + c Korsmeyer-Peppas model: Q t /Q ∞ = kt n …”
Section: Methodsmentioning
confidence: 99%
“…In addition to this, zero order (eqn ( 9)), 34 Higuchi square root law (eqn ( 10)), 35 and first order (eqn ( 11)) 36 are empirical relationships for investigating the drug release mechanism, as given below:…”
Section: Drug Releasementioning
confidence: 99%
“…70 In another study, ciprofloxacin conjugated to biogenic Au NPs demonstrated enhanced bactericidal activity against Gram-negative and Gram-positive bacteria. 71 Ciprofloxacin, adsorbed in Au NPs, showed a characteristic release over an extended period of time. 72 Ciprofloxacin capping with metallic (Ag and Au) NPs under optimized conditions significantly implicated an improved solubility, pharmacokinetics, bioavailability, and a significant antibacterial activity.…”
Section: Ciprofloxacin-conjugated Metallic Nanoparticlesmentioning
confidence: 99%